The Position of Property Rights over Flats as Collateral for Debts Charged with Dependent Rights in Semarang City: Kedudukan Hak Milik Atas Satuan Rumah Susun Sebagai Jaminan Hutang Yang Dibebankan dengan Hak Tanggungan di Kota Semarang - Diwasasri, Muhammad Titan; Suhadi, Suhadi (Annual Review of Legal Studies, 2024)
As the owner of the ownership rights to an apartment unit whose ownership is proven by a Certificate of Ownership of the Apartment, the owner of the apartment can apply for credit by using the Certificate of Ownership Rights for the apartment unit he owns as collateral for credit at the bank. With the imposition of mortgage rights on the ownership rights of apartment units in Semarang Tengah District, Kembangsari Village, Semarang City. Taking the problem formulation: (1) Why is the ownership right to the flat unit Kel. Kembangsari, District. Central Semarang, Semarang City used as debt collateral? and (2) What is the procedure for imposing an ownership certificate on an apartment unit, Ex. Kembangsari, District. Central Semarang, Semarang City, burdened with mortgage rights? The method used is a qualitative descriptive legal research method with a sociological juridical approach. The data collected is primary data and secondary data. Data validity using source triangulation techniques. The research results show: (1) Requirements and procedures for guaranteeing ownership certificates for condominium units, Kel. Kembangsari, District. Central Semarang, Semarang City as collateral in a banking credit agreement, namely a certificate of ownership of an apartment unit must meet the requirements for economic value and juridical value. Meanwhile, the procedures in SHMSRS guarantee are stages that have been determined in an organized manner and must be fulfilled for the sake of smoothness and security between debtors and creditors, consisting of the credit application stage, data analysis stage, credit implementation stage, guarantee stage, and credit expiration stage. In these stages, there are several parties who have roles and duties to ensure that the credit is implemented properly, including the bank, the notary/PPAT, and the Land Office. (2) Procedure for Imposing Ownership Certificates on Flat Units in Kel. Kembangsari, District. Central Semarang, Semarang City is closely related to agreements or contracts between legal subjects, namely creditors and debtors regarding debt agreements in the form of, for example, bank credit, with the Ownership Certificate being used as collateral for the debt with the consequence that if the debtor breaks his promise or defaults, then the guarantee is can be executed to take repayment of the debt. The encumbrance procedure is related to the registration mechanism, making Certificates of Ownership Rights for Flats in Kel. Kembangsari, District. Central Semarang, Semarang City, Power of Attorney to Encumber Mortgage Rights, and others.